2021
DOI: 10.1002/chem.202101728
|View full text |Cite
|
Sign up to set email alerts
|

Quadruple Role of Pd Catalyst in Domino Reaction Involving Aryl to Alkyl 1,5‐Pd Migration to Access 1,9‐Bridged Triptycenes

Abstract: A Pd‐catalyzed domino reaction of 1,8,13‐tribromo‐9‐methoxytriptycenes is reported. Under conventional Suzuki coupling conditions, the triptycenes underwent multiple transformations to give 1,9‐bridged triptycenes. Based on mechanistic investigations, a single Pd catalyst functions as Pd0, PdII and PdIV species to catalyze four distinct processes: (1) aryl to alkyl 1,5‐Pd migration, (2) intramolecular arylation, (3) homocoupling of phenylboronic acid and (4) Suzuki coupling. DFT calculations revealed that 1,5‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…[22] During their consequent study on the same coupling of 9-methoxyl analogue 46 b, unexpectedly, 1,9-bridged triptycene 48 b was obtained selectively, instead the formation of expected triaryltriptycene 47 b was not detected (Scheme 12b). [23] Along with the reaction condition experiments, the authors found that the formation of bromo- Based on these observations, the authors proposed a plausible catalytic cycle account for the formation of 48, in which the palladium catalyst might play a quadruple role in the whole process. According to deuterium labeling experiments, aryl-to-alkyl 1,5-palladium migration (from 49 to 51) might proceeded through either σ-bond metathesis via a palladium(II) transition state 50 a or oxidative addition via a palladium(IV) intermediate 50 b (vide supra) with hydrogen atom completely retained.…”
Section: Aryl-to-alkyl Migrationmentioning
confidence: 93%
See 1 more Smart Citation
“…[22] During their consequent study on the same coupling of 9-methoxyl analogue 46 b, unexpectedly, 1,9-bridged triptycene 48 b was obtained selectively, instead the formation of expected triaryltriptycene 47 b was not detected (Scheme 12b). [23] Along with the reaction condition experiments, the authors found that the formation of bromo- Based on these observations, the authors proposed a plausible catalytic cycle account for the formation of 48, in which the palladium catalyst might play a quadruple role in the whole process. According to deuterium labeling experiments, aryl-to-alkyl 1,5-palladium migration (from 49 to 51) might proceeded through either σ-bond metathesis via a palladium(II) transition state 50 a or oxidative addition via a palladium(IV) intermediate 50 b (vide supra) with hydrogen atom completely retained.…”
Section: Aryl-to-alkyl Migrationmentioning
confidence: 93%
“…In 2019, Shindo and coworkers reported a palladium‐catalyzed triple Suzuki coupling of 9‐hydroxy‐1,8,13‐tribromotriptycene 46 a (Scheme 12a) [22] . During their consequent study on the same coupling of 9‐methoxyl analogue 46 b , unexpectedly, 1,9‐bridged triptycene 48 b was obtained selectively, instead the formation of expected triaryltriptycene 47 b was not detected (Scheme 12b) [23] . Along with the reaction condition experiments, the authors found that the formation of bromotriptycene 49 b could be formally suppressed by extending the reaction time, while the yield of 48 b was increased, which suggested 49 b was a reaction intermediate for 48 b .…”
Section: 5‐palladium Migration Reactionsmentioning
confidence: 99%
“…More interestingly, the silicon atom seems to play an indispensable role for this migration to occur, since the reaction of a carbon analogue failed to give the desired product under otherwise identical conditions [5f] . Very recently, Iwata and Shindo also described an aryl to alkyl 1,5‐palladium migration process, and applied this strategy for 1,9‐bridged triptycene synthesis [5g] . Despite of these advances, in view of the significance for selective remote C−H bond activation, the discovery of other type 1,5‐palladium migration events are still of great value.…”
Section: Introductionmentioning
confidence: 99%
“…The 1,2-Pd II shift via a β-H elimination and reinsertion sequence, 1,4-Pd II shift, and, to a lesser extent, the 1,5-Pd II migration via C–H activation are well-established. However, to the best of our knowledge, there is only one example of 1,3-Pd II shift reported by Wolfe .…”
mentioning
confidence: 96%